Filamentous nuclear actin regulation of PML NBs during the DNA damage response is deregulated by prelamin A - Andrew M. Cobb; Shanelle A. De Silva; Robert Hayward; Karolina Sek; Svenja Ulferts; Robert Grosse; Catherine M. Shanahan (Cell Death and Disease, 2022)
Abstract Nuclear actin participates in a continuously expanding list of core processes within eukaryotic nuclei, including the maintenance of genomic integrity. In response to DNA damage, nuclear actin polymerises into filaments that are involved in the repair of damaged DNA through incompletely defined mechanisms. We present data to show that the formation of nuclear F-actin in response to genotoxic stress acts as a scaffold for PML NBs and that these filamentous networks are essential for PML NB fission and recruitment of microbodies to DNA lesions. Further to this, we demonstrate that the accumulation of the toxic lamin A precursor prelamin A induces mislocalisation of nuclear actin to the nuclear envelope and prevents the establishment of nucleoplasmic F-actin networks in response to stress. Consequently, PML NB dynamics and recruitment to DNA lesions is ablated, resulting in impaired DNA damage repair. Inhibition of nuclear export of formin mDia2 restores nuclear F-actin formation by augmenting polymerisation of nuclear actin in response to stress and rescues PML NB localisation to sites of DNA repair, leading to reduced levels of DNA damage.